Pharmacogenetic Analysis of the Model‐Based Pharmacokinetics of Five Anti‐HIV Drugs: How Does This Influence the Effect of Aging?. Issue 2 (3rd December 2017) - Chen, Jingxian; Akhtari, Farida S.; Wagner, Michael J.; Suzuki, Oscar; Wiltshire, Tim; Motsinger‐Reif, Alison A.; Dumond, Julie B.
Abstract: Analysis of aging and pharmacogenetics (PGx) on antiretroviral pharmacokinetics (PKs) could inform precision dosing for older human HIV‐infected patients. Seventy‐four participants receiving either atazanavir/ritonavir (ATV/RTV) or efavirenz (EFV) with tenofovir/emtricitabine (TFV/FTC) provided PK and PGx information. Aging‐PGx‐PK association and interaction analyses were conducted using one‐way analysis of variance (ANOVA), multiple linear regression, and Random Forest ensemble methods. Our analyses associated unbound ATV disposition with multidrug resistance protein (MRP)4, RTV with P‐glycoprotein (P‐gp), and EFV with cytochrome P450 (CYP)2B6 and MRP4 genetic variants. The clearance and cellular distribution of TFV were associated with P‐gp, MRP2, and concentrative nucleoside transporters (CNTs), and FTC parameters were associated with organic cation transporters (OCTs) and MRP2 genetic variants. Notably, p16 INK4a expression, a cellular aging marker, predicted EFV and FTC PK when genetic factors were adjusted. Both age and p16 INK4a expression interacted with PGx on ATV and TFV disposition, implying potential dose adjustment based on aging may depend on genetic background.